GPCALMA: a Grid-based Tool for Mammographic Screening - Cerello, P.; Bagnasco, S.; Bottigli, U.; Cheran, S. C.; Delogu, P.; Fantacci, M. E.; Fauci, F.; Forni, G.; Lauria, A.; Lopez Torres, E.; Magro, R.; Masala, G. L.; Oliva, P.; Palmiero, R.; Ramello, L.; Raso, G.; Retico, A.; Sitta, M.; Stumbo, S.; Tangaro, S.; Zanon, E. (Methods of Information in Medicine, 2005)
Objectives: The next generation of high energy physics (HEP) experiments requires a GRID approach to a distributed computing system: the key concept is the Virtual Organisation (VO), a group of distributed users with a common goal and the will to share their resources.Methods: A similar approach, applied to a group of hospitals that joined the GPCALMA project (Grid Platform for Computer Assisted Library for MAmmography), will allow common screening programs for early diagnosis of breast and, in the future, lung cancer. The application code makes use of neural networks for the image analysis and is useful in improving the radiologists' diagnostic performance. GRID services allow remote image analysis and interactive online diagnosis, with a potential for a relevant reduction of the delays presently associated with screening programs.Results and Conclusions: A prototype of the system, based on AliEn GRID Services [1], is already available, with a central server running common services [2] and several clients connecting to it. Mammograms can be acquired in any location; the related informatio required to select and access them at any time is stored in a common service called Data Catalogue, which can be queried by any client. Thanks to the PROOF facility [3], the result of a query can be used as input for analy-sis algorithms, which are executed on the nodes where the input images are stored,. The selected approach avoids data transfers for all the images with a negative diagnosis and allows an almost real time diagnosis for the set of images with high cancer probability.
Keywords: Grid; mammogram; screening; virtual organization